Imagery in William Allingham Poems Entitled “a Dream, the Eviction and Robin Redbreast” - Ana Mariana; Nadia Ismail; Dahlia Husain (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
The purpose of this research is to find imagery in William Allingham poems. The method used in analysis this research is descriptive qualitative and technique analyzing data. The analysis of the imagery is intended to deliver a message from the author in order to feel what is felt by the senses of the author contained in his poetry. In addition, the imagery is intended to enable the reader to obtain a concrete picture of what the author or poet wants to convey. Based on research conducted, there are five imagery contained in William Allingham's poem with the title ‘’A Dream, The Eviction and Robin Redbreast” those are visual, tactile, auditory, gustatory and olfactory imagery.